Development of Empirical Model for the Impact of Motorcycle Front Wheel-Tyre Assembly - Tan, Kean Sheng (2004)
In engineering terms, the residual deformation on structural component is correlated to the dissipated energy, the change of momentum, or the change of speed during the impact. Many force-deflection models have been successfully developed for automobiles. However, such engineering model is not well developed for two-wheel motor vehicles due to lack of correlation information between the change of velocity and the structural damage, especially the frontal components such as wheel-tyre assembly which encounter the first and direct impact in frontal collision. The present study has thus been conducted which intended to lay out a route for developing the empirical models for motorcycle front wheel-tyre assembly that can be utilized to assess the impact velocities or change of velocities of a motorcycle in frontal collision based on the post-impact residual deformation of the wheel-tyre assembly.